(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The article introduces some lines of work related to photography, archive and memories of the recent past in Argentina, particu- larly images produced in the clandestine detention center of the Information Department of the Cordoba Police. We will analyse some of the questions raised by the transition from police archives to memory archives: its testimonial status, its treatment, and its subjective, ethical and political implications. Considering its temporality and its historic legibility we examine its irreducible dimension, the dislocation that emerges between all or nothing and its consistency at present time.